Hedione Reduces Subjective Vicarious Stress - Pützer, Anika; Brüne, Martin; Hatt, Hanns; Wolf, Oliver T. (Frontiers in Behavioral Neuroscience, 2020)
Observing another person in a stressful situation can cause a full-blown physiological stress response in the observer, which is referred to as empathic stress. One way through which stress-related information might be transmitted between individuals in conditions of empathic stress is chemosensory communication. In the present study, we investigated whether the odorant Hedione, as a potential chemosignal, affects the empathic stress response at a physiological and psychological level. For this purpose, two experiments were designed, each testing one group of participants in an odor-free room and a second group in a room scented with Hedione. In Experiment 1, 60 participants (25 male) watched a video of an unknown female participant in the Trier Social Stress Test (TSST). In Experiment 2, 37 free-cycling females watched a live video of a male participant in the TSST. Observer’s psychological and physiological stress response was captured via repeated measurements of salivary cortisol, alpha-amylase and self-report ratings. Empathy with the stressed participants was assessed on the dimensions personal distress and empathic concern of the Emotional Response Scale. Our results show no substantial physiological stress response in the observers and no effect of Hedione on physiological stress measures. Further, in Experiment 1, there was no subjective stress elicited by the video and no effect of Hedione. In Experiment 2, the observation was perceived as stressful and Hedione reduced subjective vicarious stress. The subjective stress response was associated with observer’s direct personal distress, but not with their empathic concern for the target in both experiments. Based on the findings presented above, we conclude that under conditions of empathic stress, Hedione alleviates subjectively perceived stress felt when observing another person being stressed, while leaving empathic concern for the target unaffected. In this regard, future research is warranted to clarify the underlying mechanisms, as well as functional aspects of this effect.